2007
DOI: 10.1038/sj.eye.6702982
|View full text |Cite
|
Sign up to set email alerts
|

A PAX6 gene polymorphism is associated with genetic predisposition to extreme myopia

Abstract: Purpose The PAX6 gene is a homeobox gene involved in oculogenesis, ocular growth, and form-deprivation myopia. Our aim was to determine whether PAX6 polymorphism at position À12 of intron 9 (IVS9-12C to T, rs667773) is associated with high myopia in Chinese Taiwanese. Methods This case-control study compared a study group (n ¼ 188) with high myopia whose spherical equivalent was greater than À6.0 D with a control group (n ¼ 85) whose spherical equivalent was less than À0.5 D. Genotyping of IVS9-12C to T was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 22 publications
1
21
0
Order By: Relevance
“…The present study demonstrates that a novel functional SNP at PAX6 may influence an individual's susceptibility to extreme myopia. Our finding for the PAX6 gene is consistent with two previous reports on high 16,24 and extreme myopia 15 in the Chinese population.…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…The present study demonstrates that a novel functional SNP at PAX6 may influence an individual's susceptibility to extreme myopia. Our finding for the PAX6 gene is consistent with two previous reports on high 16,24 and extreme myopia 15 in the Chinese population.…”
Section: Discussionsupporting
confidence: 95%
“…When there is no evidence of dominance, we prefer to not collapse heterozygotes with minor homozygotes unless the number of minor homozygotes is too small. Because the genetic effect may be more prominent for extreme myopia as indicated by a previous study, 15 we also conducted exploratory analyses by reclassifying cases with different refractive errors.…”
Section: Statistical Analysis For Genetic Polymorphism Studiesmentioning
confidence: 99%
“…67 More interesting, the researchers in Taiwan reported strong association of extremely high myopia with PAX6 in a small case-control sample, whereas no association was found if the analysis also included subjects with less extreme myopia. 68 Of interest, the positive SNP (rs667773) reported in their study was also located in the 3Ј region of the PAX6 gene (intron 9), where potential variants responsible for susceptibility to high myopia might exist as discussed earlier. Therefore, we also tested SNP rs667773 in our high-myopia samples.…”
Section: Genetic Association Analysismentioning
confidence: 93%
“…Two studies (one American and one British) reported negative association of PAX6 with common myopia, 65,66 whereas studies in Australian and Taiwan Chinese populations suggested association for PAX6 with high myopia. 67,68 It is not surprising that the conclusions of these recent reports are equivocal due to the complex etiology of myopia. In particular, the researchers in Australia reported association of some specific mutations in the PAX6 gene with highly myopic subjects.…”
Section: Genetic Association Analysismentioning
confidence: 93%
“…[32][33][34] In addition, many candidate genes associated with high myopia have been reported. [35][36][37][38][39][40][41][42][43] However, most of these associated candidate genes have been negated by subsequent studies, and no genes have yet been identified that are consistently responsible for either common or high myopia.…”
mentioning
confidence: 99%